Severe Group C Streptococcus infection in a veterinarian. (2021) - Miles, Bryan; Tuomela, Krista; Sanchez, Joyce
Abstract: Group C Streptococcus (GCS) is part of the normal commensal flora of the upper airway, as well as frequently colonizes the skin, gastrointestinal tract, and female genital tract. It can also be implicated in mono- and polymicrobial infections of the skin and soft tissue, pharyngitis, bacteremia, endocarditis, septic arthritis, osteomyelitis, and meningitis. Our case study features a previously healthy 65-year-old male, who retired as a veterinarian one month prior, with Group C Streptococcus bacteremia complicated by septic polyarthritis, native mitral valve endocarditis, and lumbar discitis/osteomyelitis.